2022
DOI: 10.1101/2022.04.19.488750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bats as ecosystem engineers in iron ore caves in the Carajás National Forest, Brazilian Amazonia

Abstract: Ecosystem engineers are organisms able to modify their environment by changing the distribution of materials and energy, with effects on biotic and abiotic ecosystem components. Several ecosystem engineers are known, but for most of them the mechanisms behind their influence are poorly known. We detail the role of bats as ecosystem engineers in iron ore caves in the Carajás National Forest, Brazilian Amazonia, an area with > 1,500 caves, some holding ∼150,000 bats. We analyzed the chemical composition of gu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…The majority of studies focusing on Rhabdoviridae , and more specifically on the Rabies virus (RABV), were likely motivated by concerns about fatal spillover events to humans in Brazil once different bat species are described as important RABV reservoir(3436). Few studies (1-3) have focused on Orthomyxoviridae, Paramyxoviridae, Hantaviridae, Herpesviridae and Adenoviridae ( Supplementary File 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies focusing on Rhabdoviridae , and more specifically on the Rabies virus (RABV), were likely motivated by concerns about fatal spillover events to humans in Brazil once different bat species are described as important RABV reservoir(3436). Few studies (1-3) have focused on Orthomyxoviridae, Paramyxoviridae, Hantaviridae, Herpesviridae and Adenoviridae ( Supplementary File 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have also found differences in the number and species recorded as positive for a viral infection/exposure. In the review compiled database we found 31 families in 62 of the 95 bat species studied representing 5 of 9 chiropteran families living in Brazil: Phyllostomidae (38), Molossidae (14), Vespertilionidae (9), Mormoopidae (2) and Emballonuridae (1). In the ZOVER database, evidence of infection was recorded for 22 virus families in 58 of 95 bat species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bats (order Chiroptera ) compose the second most diverse mammalian order with 1,456 known species from 21 families ( https://batnames.org ) that participate in diverse ecological processes such as plant pollination, seed dispersion, and soil renewal up to habitat modifications ( 1 ). Bats are also reservoirs of a large diversity of zoonotic and nonzoonotic viruses ( 2 to 4 ).…”
Section: Introductionmentioning
confidence: 99%